Vietnam’s transition to low-emission food systems: 2025 country profile – 2nd Edition - Martius, C.; Vu, T.P.; Pingault, N.; Pham, T.T.; Wassmann, R.; Guérin, L.; Mwambo, F.; Nhuong, T.; Yee, C.C. (CIFOR-ICRAF, 2025)
The global food system is responsible for 23 – 42% of total net anthropogenic emissions. This share will likely increase in the future, driven by population and economic growth and changes in lifestyle, as other economic sectors are progressively decarbonized. Without rapid and radical transformations in food systems, the Paris Agreement targets will likely remain out of reach. Data on GHG (greenhouse gas) emissions and removals are usually collected and analyzed across five economic sectors (energy, industry, agriculture, LULUCF (Land Use Land Use Change and Forestry) and waste). This makes it hard to identify and estimate food system emissions, which span across all these sectors.